Molecular characterization of response to arsenic in rice (Oryza sativa L.) - Nam, Trinh Ngoc; Thia, Le Hong; Tuan, Nguyen Vuong (Academia Journal of Biology, 2015)
Arsenic (As) is classified as one of toxic metalloids, that directly affects to most plants. Moreover, As is also a human carcinogen due to drinking As-contaminated groundwater or eating plant food including rice cultivated in polluted areas. The effect of As on rice growth was established, but the precised mechanism of rice response to As remains to be elucidated. This study investigated the biochemical and molecular changes in roots of rice seedlings under As stress. A 100 mM As(III) solution strongly inhibited the growth and induced reactive oxygen species (ROS) production in rice roots. Using ICP-MS, we found As content in rice roots increased with increasing concentration of As solution treatment. Semi-quantitative RT-PCR analysis revealed that some ROS-related gene, protein kinase-related genes, signal transduction-related genes, transcription factor-related genes and auxin synthesis-related gene were up-regulated during As stress. However, cell cytokinesis-related gene was down-regulated. Polyacrylamide gel electrophoresis and activity-gel assay showed that enzymatic activity of superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD) were strongly induced under As stress, as an antioxidant defense system. In addition, the contrileuted to elucidating increase of proline content, function as radical scavenger and cellular redox potential buffer, was found in As treated rice roots. Our findings more or less on the biochemical and molecular mechanism in response to As stress in plants